Outdoor recreation, nature-based tourism and food: experiences and adaptations in the hospitality industry during the COVID-19 pandemic—a review - Calvén, Anna; Beery, Thomas; Kristofers, Hannah; Johansson, Marcus; Carlbäck, Mats; Wendin, Karin (Frontiers in Sustainable Tourism, 2025)
During the COVID-19 pandemic, participation in outdoor recreation increased in several countries, with nature taking on an expanded role as a social space for meetings and activities with food. This development may have created opportunities for nature-based hospitality providers to navigate the pandemic crisis. This review examines how food and eating were part of outdoor recreation and nature-based tourism during COVID-19, focusing on hospitality providers in rural Sweden. A literature search was performed for research articles, newspapers, and magazine articles. The results show creativity in adapting to new outdoor and nature tourism situations. The main findings that emerged focused on local and national guests, preventing the spread of infection, food as part of the experience in nature, experience packages, comfort, local food, food trucks and takeaway food, and other hospitality industry changes. Trends observed before COVID-19 but accelerating during the pandemic were also highlighted. Further research is needed to improve our understanding of food as part of outdoor recreation and nature-based tourism and how this knowledge can support sustainable thinking in the hospitality sector while contributing to resilient rural development.